2020
DOI: 10.3390/ijms21239281
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine-Mediated Anxiolytic-Like Effect: Interplay with Adenosine A1 and A2A Receptors

Abstract: Acute or chronic administration of guanosine (GUO) induces anxiolytic-like effects, for which the adenosine (ADO) system involvement has been postulated yet without a direct experimental evidence. Thus, we aimed to investigate whether adenosine receptors (ARs) are involved in the GUO-mediated anxiolytic-like effect, evaluated by three anxiety-related paradigms in rats. First, we confirmed that acute treatment with GUO exerts an anxiolytic-like effect. Subsequently, we investigated the effects of pretreatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…So, despite the general idea that Guo-stuffed exosomes are released for the endocrine purpose has to be confirmed, it seems fairly possible. Recently, several studies have reported the involvement of Guo-mediated signaling in behavioral outcomes, such as neuroprotection, and anxiolytic-like and analgesic effects (Almeida et al, 2017;Frinchi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…So, despite the general idea that Guo-stuffed exosomes are released for the endocrine purpose has to be confirmed, it seems fairly possible. Recently, several studies have reported the involvement of Guo-mediated signaling in behavioral outcomes, such as neuroprotection, and anxiolytic-like and analgesic effects (Almeida et al, 2017;Frinchi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to the results of Dal-Cim et al, who indicate that some neuroprotective effects may be conducted via A 2A R but not A 1 R [68]. Some studies suggest that it is the interplay between coexpressed receptors and the fine-tuning mechanism that are responsible for the neuroprotective effect [64,69].…”
Section: Guanosine-specific Targets: Receptors and Binding Sitesmentioning
confidence: 57%
“…Indeed, there is a general consensus about GBPs behaving as a repair system upon brain injury in both in vitro and in vivo models (Lanznaster et al, 2016;Ribeiro et al, 2016). Accordingly, 1) higher extracellular levels of GBPs but not ABPs are detected in cultured astrocytes upon hypoxic or hypoglycaemic conditions (Ciccarelli et al, 1999) ii) GBPs, especially GUO, interferes with glutamatergic system by preventing glutamate excitotoxicity (Tasca et al, 2004;Lanznaster et al, 2017); iii) GBPs demonstrate anxiolytic, antidepressant and anticonvulsant effects (Tavares et al, 2008;Kovacs et al, 2015;Bettio et al, 2016;Frinchi et al, 2020); iv) GUO administration prevents NMDA-evoked neurotoxicity and apoptosis in hippocampal slices (Molz et al, 2008), inhibits the neurotoxin 6hydroxydopamine (6-OHDA)-mediated apoptosis in a model of Parkinson's disease (Giuliani et al, 2012b), induces neuroprotection in hippocampal slices subjected to oxygen/ glucose deprivation (OGD) and ischemia (Ganzella et al, 2012;Dal-Cim et al, 2013); v) GUO stimulates neural stem cells and astrocyte proliferation (Ciccarelli et al, 2000;Su et al, 2013), as well as neurogenesis (Bau et al, 2005;Decker et al, 2007;Piermartiri et al, 2020); vi) GTP induces differentiation of C2C12 skeletal muscle cells and PC12 cells via Ca 2+ -activated K + channel, upon phospholipase C (PLC)/ inositol triphosphate (IP3)/diacylglycerol (DAG) activation (Gysbers and Rathbone, 1996;Guarnieri, Fanò et al, 2004;Pietrangelo, Fioretti et al, 2006;Mancinelli, Pietrangelo et al, 2012) vii) GUA improves learning and memory formation (Giuliani et al, 2012a;Zuccarini et al, 2018b).…”
Section: Roles Of Gbps In the Cnsmentioning
confidence: 99%